Effect of Glucose Specific lectins, Alkaloid and Volatile Oil Extracted From Nigella Sativa L Seeds in Blood Glucose Level In Normal Rabbits: Kahtan A.Al-mzaien , Ekhlass H.ALAssadi - Al-mzaien, Kahtan A. (The Iraqi Journal of Veterinary Medicine, 2006)
This study was conducted to investigate the hypolycemic effect of the aqueousextract and some active ingredients of Nigella Sativa seeds in normal rabbits. Twentyfour male rabbits were divided into six equal groups. The first five groups were receivedby gavage needle 160,240,320,400 and 480 mg/kg B.W. of the aqueous extract, whilethe sixth group which served as control received normal saline solution. After two hoursof administration, the group which received 320 mg showed the lowest blood sugar levelas compared to control and other treated groups. This dose was considered for the nextstudies.Lectin was isolated from Nigella Sativa seeds by 0.2M phosphate buffer containing0.15M NaCl at pH 7.0, and the activity were measured by hemagglutination method.Glucose specific lectin , was purified by affinity chromatography on sephadex G-50,using 0.02M phosphate buffer containing 0.15M NaCl and 0.05M glucose,PH 7.0 aseluent. The obtained results was indicated the presence of 504 glucose specific lectinunits activity /320 mg extract which represented 12.9% of the total lectin units activity,with a time of purification of 69.8.A group of male rabbits (n=5) which was received orally after 12h of fasting504 glucose specific lectin units activity/Kg.B.W. showed a significant decline in bloodglucose level as compared with control one.Oral administration of Nigella Sativa seeds crude alkaloid to four groups (n=4) ofrandomly divided male rabbits after 12h of fasting and, at a level of 14,21,28 and 35 mg/kg B.W revealed a significant decline (p<0.01) in blood glucose concentration ascompared to the control and other treated groups.Also, the results of this study showed that, administration of Nigella Sativaseeds volatile oil to four equal groups (n=4) of randomly divided male rabbits at a levelof 5,8,11 and 14 mg\Kg B.W. caused a significant decline in blood glucoseconcentration as compared to the control and treated groups.